045. The Prevalence and Overview of Cholelithiasis at Achmad Mochtar Hospital, Bukittinggi - Abror, Muhammad; Manjas, Ambiar (JBN (Jurnal Bedah Nasional); Vol 8 No 2 (2024): Proceeding The 2nd National Conference of Indonesia Surgical EducationDO - 10.24843/JBN.2024.v08.is02.p045, 2024)
Background : Cholelithiasis (gallstone disease) is one of the most common diseases of the digestive tract.1 The incidence of Cholelithiasis in Indonesia certainly unknown, in China the incidence of all diseases is 10.7% and in Asia 3-10%.2 The risk factors for cholelithiasis have been generally known, namely the four "F": female, fat, forty, and fertile, (female, obesity, age 40 years, fertile age).3 Achmad Mochtar Hospital is a Provincial Hospital located in Bukittinggi city area which is famous for its history and cuisine. This study aims to obtain a profile of Cholelithiasis within the scope of Achmad Mochtar Hospital Bukittinggi. Methods : This study is a descriptive cross-sectional study. The subjects of the study were taken from medical record data of Cholelithiasis patients at Achmad Mochtar Hospital Bukittinggi in August 2023 - June 2024 that get in the inclusion criteria, all Cholelithiasis patients recorded in the medical records at Achmad Mochtar Hospital Bukittinggi in August 2023 - June 2024. The research variables are age, gender, and patient address. All data obtained are then analyzed using SPSS version 23 for Windows. Results: the results of the study obtained a total of 197 patients with ages <40: 56 (28%), and >40 : 141 (72%). The majority of patients are women 125 (63%) and men 72 (36%), demographically the most patients are from the Bukittinggi city (26%). Conclusion: Cholelithiasis patient at Achmad Mochtar Hospital Bukittinggi August 2023 - June 2024 were 197 people, the majority were aged >40 years with women being the most patient and a lot of patient come from Bukittinggi suspected because Bukittinggi is tourism city.